Gigged: the end of the job and the future of work - Kessler, Sarah (New York, 2018)
"The full-time job is disappearing―is landing the right gig the new American Dream? One in three American workers is now a freelancer. This “gig economy”―one that provides neither the guarantee of steady hours nor benefits―emerged out of the digital era and has revolutionized the way we do business. High-profile tech start-ups such as Uber and Airbnb are constantly making headlines for the disruption they cause to the industries they overturn. But what are the effects of this disruption, from Wall Street down to Main Street? What challenges do employees and job-seekers face at every level of professional experience? In the tradition of the great business narratives of our time, Gigged offers deeply-sourced, up-close-and-personal accounts of our new economy. From the computer programmer who chooses exactly which hours he works each week, to the Uber driver who starts a union, to the charity worker who believes freelance gigs might just transform a declining rural town, journalist Sarah Kessler follows a wide range of individuals from across the country to provide a nuanced look at how the gig economy is playing out in real-time. Kessler wades through the hype and hyperbole to tackle the big questions: What does the future of work look like? Will the millennial generation do as well as their parents? How can we all find meaningful, well-paid work?"